Yoga for dummies - Payne, Larry; Feuerstein, Brenda; Feuerstein, Georg (--For dummies., 2023)
Stretch, strengthen, and start your yoga journey with this approachable guide. Yoga For Dummies teaches beginners the fundamentals of Yoga--correct posture, breathing techniques, meditation practices, and beyond. It's also a helpful resource for established yogis who want to focus on foundations. Whoever you are, you'll enjoy the proven mental and physical health benefits of this ancient practice. Improve cardiovascular health, lower blood pressure, increase your flexibility and balance, reduce stress, and more! Let Dummies help you get the most out of your yoga routine. This edition includes updated photos, new mindfulness meditations, new routines, and easy-to-follow instructions for mastering core yoga poses and building a regular practice.